Differential Distribution Table implementation DDT survey - Eid Khamees Al-Shammary, Mohammed; Mahmood Al-Dabbagh, Sufyan Salim (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
The security of the transmitted data is one of the important issues that led to improve cryptosystems. Block ciphers as symmetric key cryptosystems are widely implemented in different applications and devices. Many algorithms had been presented that proposed new designs and enhancements for the block ciphers. Most of these papers based on the differential characteristics that provided by the Differential Distribution table DDT. The implementation of DDT had several points of advantages in design, modify and attack block cipher. Even with larger block size of some cipher families, the Partial Differential Distribution Table (PDDT) is implemented to override the big block size. The comparison results showed that both of DDT and PDDT are efficient tools that provide important differential characteristics that may implemented with accompanied of different function and deep learning models.